HOTAIR Modulated Pathways in Early-Stage Breast Cancer Progression - Abba, Martin C.; Fabre, María Laura; Lee, Jaeho; Tatineni, Pradeep; Kil, Hyunsuk; Aldaz, C. Marcelo (Frontiers in Oncology, 2021)
The long-non-coding HOX transcript antisense intergenic RNA (HOTAIR) was identified as significantly upregulated in breast ductal carcinoma in situ (DCIS). The aim of this study was to characterize the phenotypic effects and signaling pathways modulated by HOTAIR in early-stage breast cancer progression. We determined that HOTAIR induces premalignant phenotypic changes by increasing cell proliferation, migration, invasion and in vivo growth in normal and DCIS breast cell lines. Transcriptomic studies (RNA-seq) identified the main signaling pathways modulated by HOTAIR which include bioprocesses related to epithelial to mesenchymal transition, cell migration, extracellular matrix remodeling and activation of several signaling pathways (HIF1A, AP1 and FGFR). Similar pathways were identified as activated in primary invasive breast carcinomas with HOTAIR over-expression. We conclude that HOTAIR over-expression behaves as a positive regulator of cell growth and migration both in normal and DCIS breast cells involved with early-stage breast cancer progression.